The use of stoned olive cake and rolled linseed in the diet of intensively reared lambs: effect on the intramuscular fatty-acid composition. (30th October 2013) - Mele, M.; Serra, A.; Pauselli, M.; Luciano, G.; Lanza, M.; Pennisi, P.; Conte, G.; Taticchi, A.; Esposto, S.; Morbidini, L.
Abstract : The aim of the present study was to evaluate the effect of the inclusion of stoned olive cake and rolled linseed in a concentrate-based diet for lambs on the fatty-acid composition of polar and non-polar intramuscular lipids of the longissimus dorsi muscle. To achieve this objective, 32 Appenninica lambs were randomly distributed into four groups of eight lambs each and were fed conventional cereal-based concentrates (diet C); concentrates containing 20% on a dry matter (DM) basis of rolled linseed (diet L); concentrates containing 35% DM of stoned olive cake (diet OC); and concentrates containing both rolled linseed (10% DM) and stoned olive cake (17% DM; diet OCL). The concentrates were administered together with grass hay at a 20:80 forage:concentrate ratio. Growing performances and carcass traits were evaluated. The fatty-acid composition was analysed in the total intramuscular lipids, as well as in the polar and neutral lipids. The average feed intake and the growth performance of lambs were not affected by the dietary treatments, as a consequence of similar nutritional characteristics of the diets. The inclusion of rolled linseed in the L and OCL diets increased the content of C18:3 n-3 in intramuscular total lipids, which was threefold higher in meat from the L lambs and more than twofold higher in meat from the OCL lambs compared with the C and OC treatments. The n-6:n-3 ratio significantly decreased in the meat from lambs in the L and OCL groups, reaching values below 3. The L treatment resulted in the highest level of trans -18:1 fatty acids in the muscle. Regardless of the dietary treatment, the t 10-18:1 was the major isomer, representing 55%, 45%, 49% and 45% of total trans -18:1 for C, L, OC and OCL treatments, respectively. Neutral lipids from the OC-fed lambs contained the highest amount of c 9-18:1 (more than 36% of total fatty acids); however, the content of c 9-18:1 did not differ between the OC and C lambs, suggesting an intensive biohydrogenation of dietary c 9-18:1 in the case of OC treatment. The highest content of c 9, t 11-18:2 was detected in the intramuscular fat from the L-fed lambs, followed by the OCL treatment. A similar trend was observed in the neutral lipid fraction and, to a lower extent, in the polar lipids.